(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2026)
The use of energy sources with a lower environmental impact has been growing worldwide, focusing on energy transition and sustainable development. However, there is still a need for actions to disseminate theoretical and experimental knowledge involving the operation and use of technologies associated with renewable energy sources. Seeking to disseminate knowledge to students at various levels of education, this paper presents the methodology used and results obtained in executing a teaching project on applying photovoltaic solar energy. The project developed aims to pass on knowledge through the development of a solar lantern prototype for high school, technical school and newly admitted higher education students in the city of Belém-PA and high school students in a remote riverside community in the interior of the municipality of Abaetetuba-PA. The desire is to expand students’ interest in the subject so that they seek to deepen and, eventually, develop new prototypes using photovoltaic solar energy. In the workshops, participants are initially submitted to a presentation of the operating principles of the components used, as well as fundamental concepts in electrical engineering (electrical circuits, electronics and photovoltaic solar generation). In the practical part, students are divided into groups to make the prototype and perform the necessary measurements of electrical parameters to verify its operation. So far, the project has reached around 130 students who, through the responses presented in the forms applied, demonstrate satisfaction and good acceptance of the actions carried out in the workshop.